A Review of the Use of Chestnut in Traditional and Innovative Food Products - Raquel P. F. Guiné; Cátia Costa; Sofia G. Florença; Paula M. R. Correia (Journal of Nuts, 2023)
Chestnuts have been consumed in Portugal for immemorial times. These fruits are highly appreciated, not only due to their organoleptic characteristics but also due to their nutritional and functional values. For the nutrients to be more accessible and for the chestnuts to have better flavour and digestibility, it is necessary to heat, cook or roast them, for example. Chestnuts are a very versatile food, in terms of preparation, and can be cooked, roasted, as an accompaniment to dishes, replacing rice, pasta or potatoes, in the base of soups or the preparation of appetizing desserts and cakes. In Portugal the use of chestnuts to produce differentiated food products is traditional, but also new and innovative products are appearing on the market, either made with chestnuts or even with some residues of their processing, in the context of a circular economy. Examples of traditional usages of chestnut in Portugal include chestnut soup, or roasted chestnuts, which are typically consumed in the colder months of autumn and winter. In what concerns more modern trends, the use of chestnut flour to incorporate into a variety of foods, like bread, cookies or pasta is highlighted. This article explores the value of the chestnut sector in Portugal and the use of these fruits to obtain either traditional or innovative foods, such as bread, biscuits, pasta and beverages.